Chiral Phosphoric Acid‐Catalyzed Enantioselective Aza‐Friedel–Crafts Alkylation of Indoles with γ‐Hydroxy‐γ‐lactams. Issue 5 (15th March 2013) - Courant, Thibaut; Kumarn, Sirirat; He, Long; Retailleau, Pascal; Masson, Géraldine
Abstract An enantioselective aza‐Friedel–Crafts reaction of indoles with γ‐hydroxy‐γ‐lactams using a chiral phosphoric acid catalyst is reported. The approach described herein provides an efficient access to 5‐indolylpyrrolidinones in good to quantitative yields and excellent enantioselectivities (up to >99% ee). The results suggest that the reaction may proceed via N‐acyliminium intermediates associated with the chiral phosphoric acid anion.